TINGKAT KESEJAHTERAAN DAN STATUS KESIAPAN OWA JAWA DI PUSAT PENYELAMATAN DAN REHABILITASI SATWA UNTUK DILEPASLIARKAN - Yohanna .; Burhanuddin Masy'ud; Ani Mardiastuti (Media Konservasi, 2014)
Javan gibbon (Hylobates moloch Audebert 1798) is an endemic non-human primate in Java Island. Its population decreased because of  destroyed habitat and illegal hunting. One of the ex-situ conservation effort is by building Javan Gibbon Rescue and Rehabilitation Center (JGC). One of the JGC’s purpose is releasing javan gibbon which is ready. Javan gibbons management in JGC should pay attention to animal welfare of javan gibbons. The purposes of this research are knowing the level of animal welfare and preparedness status of javan gibbons for released. The used methods are direct observation to the enclosure, health and javan gibbon its self, focal animal sampling for behaviour observation and interviewing the animal keeper and veterinary. The level of animal welfare of All of the javan gibbons in JGC were in very well category. The sequence of animal welfare level of javan gibbons from the highest to the lowest based on enclosure type were made-introduction enclosure, pair enclosure, and semi-natural-introduction enclosure. The readiness status for release were known that four pairs of  javan javan gibbon   were categories very ready  (Willie-Sasa, Mel-Pooh, Moli-Nency, dan Asep-Dompu), one pair was ready (Robin-Moni) and one pair was not ready yet (Labuan-Kasy).Keywords: Animal welfare, Javan gibbon, Javan gibbon center, Released.